Ensino de ecologia por investigação: a paisagem cárstica e suas cavernas para aprender o ciclo hidrológico - Alexandra Esteves Oliveira Campos (2019)
This study focuses on teaching by research as a didactic approach to the scientific literacy of primary school students in order to support them for a reflective and active role in decision- making processes in everyday life. Studies on Science Teaching by Research (STR) show strong evidence that such an approach strongly contributes to the achievement of science teaching objectives in schools, since its centrality lies mainly in the autonomy of students in solving problems of scientific orientation. For this reason, we have developed an Investigative Didactic Sequence (IDS) based on the foundations of the STR to provide conceptual, procedural and attitudinal learning situations with the water cycle interfacing with limestone in the karst landscape being the selected context to be developed. With this work we hope to contribute to overcome the lack of didactic materials with an investigative approach and to subsidize the teacher in their implementation in ecology classes and, therefore, bring the scientific culture closer to school daily life.